Age and other perioperative risk factors for postoperative systemic inflammatory response syndrome after cardiac surgery - Dieleman, J.; Peelen, L.; Coulson, T.; Tran, L.; Reid, Christopher; Smith, J.; Myles, P.; Pilcher, D. (Oxford University Press, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the British Journal of Anaesthesia. All rights reserved. Background The inflammatory response to surgery varies considerably between individual patients. Age might be a substantial factor in this variability. Our objective was to examine the association of patient age and other potential risk factors with the occurrence of a postoperative systemic inflammatory response syndrome, during the first 24 h after cardiac surgery. Methods This was a retrospective cohort study, using linked data from the Australian and New Zealand Society of Cardiac and Thoracic Surgeons (ANZSCTS) Database and the Australian and New Zealand Intensive Care Society (ANZICS) Adult Patient Database. Data from patients who underwent coronary artery bypass grafting and/or valve surgery were used. The association between age and postoperative SIRS was analysed using Poisson regression, and corrected for other risk factors. Restricted cubic splines were used to determine relevant age categories. Results are expressed as risk ratios (RR) with 95% confidence intervals (CI). Results Data from 28 513 patients were used. In both univariable and multivariable models, increased patient age was strongly associated with reduced postoperative SIRS prevalence. Using 73-83 yr as the reference category, the RRs (95% CI) for the age categories were 1.38 (1.28-1.49) for =43 yr, 1.15 (1.09-1.20) for 44-63 yr, 1.05 (1.00-1.09) for 64-72 yr, and 1.03 (0.94-1.12) for > 83 yr, respectively. The predictive value for postoperative SIRS of the final model, however, was moderate (c-statistic: 0.61). Conclusions We have demonstrated that advanced patient age is associated with a decreased risk of postoperative SIRS among cardiac surgery patients, where patients aged over 72 yr had the lowest risk.